Money matters some puzzles, anomalies and crises in the standard macroeconomic model - Mahmud, Syed F.; Yamaguchi, Kaoru; Yülek, Murat Â. 1968- (Peter Lang Gmbh, 2017)
The 2007 financial crisis and the Great Recession have prompted a debate about the state of macroeconomics, and many orthodox economists have argued that macroeconomics has entered a Dark Age. This book discusses the shortcomings of the standard macroeconomic model (SMM). The SMM failed to explain the real world and anticipate the global financial crises. The main reasons for this failure have been attributed to its inability to assign an active role of money and by the absence of appropriate modelling of financial markets. The book also discusses how the SMM can be reformed to better account for the real world and policy prescriptions, such as the Chicago Plan, that can reduce the risks emanating from excessive money creation by banks